Factors Influencing A Business Towards Zakat Payment In Malaysia - Abdul Aziz, Abdullah; Mohd Rizuan, Abdul Kadir; Zulkifli, Zainal Abidin (2014)
Zakat is one of the five pillars in Islam. Zakat is a compulsory contribution system in Islam, taken from those who have excesses, and gives to the needy. Its principal objectives are to develop a balanced socio-economic growth, and to purify one's soul and wealth so that their wealth is blessed by Allah SWT (God). It was agreed by all Muslim scholars that businesses are subject to zakat. Zakat on business is obligatory (wajib) for companies, as long as Muslims have interests it. However, the collection of zakat from the businesses in Malaysia is still low. This might due to much reasons.This study is not looking at the business zakat non-compliance, but rather to investigate the factors that influence a company towards the zakat payment. It examine whether the company’s characteristics such as board of directors, shareholding’s ownership, size of the company and the level of profitability will motivate the zakat payment on business. The results found that none of the factors are significantly relate to the business zakat payment by businesses.